The effects of high-intensity interval training at the anaerobic and psychomotor fatigue thresholds on physiological parameters in young soccer players: a prospective study - Chmura, Paweł; Chmura, Jan; Chodor, Wiktor; Drożdżowski, Adrian; Rokita, Andrzej; Konefał, Marek (Frontiers in Physiology, 2023)
This study aimed to investigate the effects of a four-week specific high-intensity interval training (HIIT) program, performed between the anaerobic threshold (ANT) and the psychomotor fatigue threshold (PFT), on physiological parameters in 14 professional soccer players at the under-17 level. The first and second stages of the research protocol included a treadmill running exercise with increasing load and six three-minute four versus four games of soccer with a three-minute break between games. Players then participated in a training microcycle involving three specific HIIT exercises twice per week for four weeks, after which they repeated stages one and two, followed by an assessment of changes. Measurement of lactate (LA) determined the ANT, and choice reaction time (CRT) indicated the PFT among other selected physiological parameters. Repeated-measures analysis of variance (ANOVA) compared mean values for the examined variables with a Bonferroni post hoc test used. It was demonstrated significantly increased maximal oxygen consumption (VO2 max) from 45.9 ± 3.0 to 48.7 ± 2.6 at the ANT and from 49.1 ± 3.4 to 52.0 ± 3.6 on PFT after four weeks of training.A significant increase was also recorded in running speed (RS) at both thresholds, and heart rate (HR) at the ANT (p ≤ 0.05). Moreover, the players exceeded their intensity of effort during the ANT while playing four versus four soccer matches but did not reach intensity at the PFT.In conclusion, the findings of the study demonstrated that, both thresholds shifted towards higher loads, and the proposed specific HIIT effectively increased the exercise capacity of soccer players.